2015
DOI: 10.1159/000441913
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Stem Cell Therapy for Diabetic Nephropathy

Abstract: and iPSCs into renal cells and in the generation of tissue-and patient-specific iPSCs, offering a powerful tool to investigate DN mechanisms and to identify the ideal candidate cell for future clinical application. Key Message: This review provides updated information on recent progress and limitations of stem cell-based therapy for DN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 85 publications
2
32
0
Order By: Relevance
“…These contrasting results could be explained by the differences in the longterm and short-term exposures to pro-inflammatory conditions. For example, in a long-term exposure study, stem cells from the apical papilla demonstrated inhibition of osteogenesis when exposed to proinflammatory cytokines (TNF-α and interleukin 1 beta), while the cytokines induced mineralization in the short-term culture [101]. In view of all the data presented here, we can infer that BPA acts on MSCs exhibiting inconsistent behavior and it is also clear that short and longterm exposure studies differ significantly.…”
Section: Osteogenic Differentiationmentioning
confidence: 65%
See 1 more Smart Citation
“…These contrasting results could be explained by the differences in the longterm and short-term exposures to pro-inflammatory conditions. For example, in a long-term exposure study, stem cells from the apical papilla demonstrated inhibition of osteogenesis when exposed to proinflammatory cytokines (TNF-α and interleukin 1 beta), while the cytokines induced mineralization in the short-term culture [101]. In view of all the data presented here, we can infer that BPA acts on MSCs exhibiting inconsistent behavior and it is also clear that short and longterm exposure studies differ significantly.…”
Section: Osteogenic Differentiationmentioning
confidence: 65%
“…MSCs have gained attention in the field of regenerative medicine because they can potentially modulate numerous incurable diseases [102]. Currently, there are 333 published studies describing the use of MSCs in clinical trials, addressing the prospective therapies for diseases such as cardiovascular disease [103], diabetic nephropathy [101], diverse brain injuries (including stroke, neural trauma, and heatstroke) [104] and lung injury [105]. These cells are widely used because of their multiple biological functions, including multi-lineage differentiation, their ability to promote tissue-repair, as well as their anti-inflammatory and immunosuppressive effects.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs have been popularly used in cell therapy, although their clinical usefulness remains restricted. MSCs of various donors are heterogeneous and in vitro cell passages and culture conditions directly affect the cell phenotype (Kretlow et al, 2008; Liu and Tang, 2015; Turinetto et al, 2016). In addition, cellular senescence significantly impairs the potential for MSC proliferation and differentiation (Turinetto et al, 2016).…”
Section: Challenges Of Using Mscs In Cell Therapymentioning
confidence: 99%
“…Microscopic changes involve the thickening of the tubular basement membrane (TBM) and glomerular basement membrane (GBM), and mesangial proliferation, glomerulotubular junction abnormalities (GTJA) and arteriosclerosis. And for the ultramicroscopic changes, podocyte effacement and decrease in its density appear to be the centerpiece of DN pathogenesis [30]. Consisting of the pivotal workload of dialysis centers throughout the world, DN is often featured by glomerulosclerosis, tubulointerstitial fibrosis as well as tubular atrophy [31], which starts with albuminuria, which can progress from microalbuminuria to macroalbuminuria [32].…”
Section: Dn and Podocytementioning
confidence: 99%